Implementation Of Halal Value Chain In The Unit Boarding Boarding Business An- Nafi'iyah Bangkalan - Moh Lutfi; Luluk Hanifah (JOURNAL OF SHARIA ECONOMICS, 2023)
Along with the majority of Indonesia's Muslim population, food development has developed and halal drinks continue to increase. Therefore it is Halal value chain is a production activity that can be guaranteed to be halal from start to finish from input, production, distribution, marketing, And consumption in produce Halal products, raw material input must be considered as well as technology processing used as well as all product procurement processes that will be consumed. The aim of this research is to find out the implementation process Halal value chains on Units Business Boarding school as well as know opportunity And obstacle on Units Business Boarding school with approach draft halal value chain that focuses on halal food. This research is research field using a qualitative approach. As for the retrieval technique data with documentation, observation and interviews with students, administrators and Caregiver Cottage (cleric). Study This done on cottage Boarding school An- Nafi'iyah Bangkalan. registered in OPOP ( one Islamic boarding school, one product ) region Madurese, with production know. Study This expected own benefit to reader And cottage Boarding school that is give outlook of the importance of implementing ecosystems Halal Value Chain in every business unit in Islamic boarding schools in Madura in particular , as well as among the community Which is developing its business unit